2014
DOI: 10.1038/nature13437
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-seq reveals dynamic paracrine control of cellular variation

Abstract: High-throughput single-cell transcriptomics offers an unbiased approach for understanding the extent, basis, and function of gene expression variation between seemingly identical cells. Here, we sequence single-cell RNA-Seq libraries prepared from over 1,700 primary mouse bone marrow derived dendritic cells (DCs) spanning several experimental conditions. We find substantial variation between identically stimulated DCs, in both the fraction of cells detectably expressing a given mRNA and the transcript’s level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
923
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 908 publications
(981 citation statements)
references
References 38 publications
(61 reference statements)
38
923
1
3
Order By: Relevance
“…Both the huge cell‐to‐cell variability and the amount of data these new technologies have brought to light constitute a great resource and at the same time a challenge for scientists. The parallel development of more sophisticated algorithms, faster computational approaches and new data visualization methods has already allowed scientists to gain new insights into immune system diversity 18, 23, 55, 56. Despite this incredible progress, there are still some issues that need to be solved and most of the works involving single‐cell sequencing are methodological.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the huge cell‐to‐cell variability and the amount of data these new technologies have brought to light constitute a great resource and at the same time a challenge for scientists. The parallel development of more sophisticated algorithms, faster computational approaches and new data visualization methods has already allowed scientists to gain new insights into immune system diversity 18, 23, 55, 56. Despite this incredible progress, there are still some issues that need to be solved and most of the works involving single‐cell sequencing are methodological.…”
Section: Discussionmentioning
confidence: 99%
“…An scRNA‐seq based study of bone marrow‐derived dendritic cell activation revealed that certain genes had a bimodal pattern of gene expression 55. Subsequent studies showed that paracrine signalling of a subset of fast‐responding dendritic cells affects the whole population 56. Future studies on other specific groups of immune cell populations (e.g.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency for detecting single transcript molecules has been estimated to be 30% [13,16] and 3% [15] respectively, which is much lower than the 85% of hybridization efficiency in sm-FISH [4,17]. Such low efficiencies currently prevent these alternative methods from surveying the transcriptome with singlemolecule sensitivity and resolution in situ [18,19].…”
Section: Alternative Methods For Rna Detection In Imagingmentioning
confidence: 99%
“…24 These authors sequenced single-cell RNA-Seq libraries from over 1,700 primary dendritic cells exposed to several experimental conditions, involving different stimuli and incubation times. Important messages of the study are that a few precocious cells react at early times to the stimulus; that variations exist in the fraction of cells expressing a defined mRNA and its relative levels; that expression profiles vary overtime; and, that stimulation of bystander cells occurs essentially by paracrine effects.…”
Section: The Advent Of Single-cell Analyses and Rna-seq Technologies:mentioning
confidence: 99%